Reaction of sugarcane genotypes to Pratylenchus brachyurus and P. zeae - Santos, Daniela A.; Dias-Arieira, Cláudia R.; Souto, Eliezer R.; Biela, Fabio; Cunha, Tatiana Pagan L. [UNESP]; Rogerio, Flavia; Silva, Tiago Roque B.; Milani, Klayton F. (My University, 2012)
The aim of the study was to evaluate the susceptibility of 30 genotypes of sugarcane to Pratylenchus brachyurus and Pratylenchus zeae nematodes under controlled conditions. The soil was infested with 500 specimens of nematodes and the final population and reproduction factor determined 60 days after inoculation. All the varieties assessed exhibited susceptibility to the nematodes. The reproduction factor for P. brachyurus ranged between 1.3 and 3.7, and for P. zeae between 1.1 and 3.8.
Keywords: Control; Resistance; Root-lesion nematode; Saccharum spp.